Identification of the Potential Metabolic Pathways Involved in the Hepatic Tumorigenesis of Rat Diethylnitrosamine-Induced Hepatocellular Carcinoma via 1H NMR-Based Metabolomic Analysis. (2nd January 2019) - Chen, Minjiang; Lu, Siming; Zheng, Hong; Xu, Min; Song, Jingjing; Yang, Weibin; Weng, Qiaoyou; Zheng, Liyun; Fan, Xiaoxi; Cheng, Xingyao; Gao, Hongchang; Ji, Jiansong
Abstract : The systemic investigation of the metabolic pathways associated with the hepatic tumorigenesis is important to discover novel biomarkers and identify the potential pathogenesis. Here, the 1 H nuclear magnetic resonance- ( 1 H NMR-) based metabolomic analysis was used to monitor the whole process of rat diethylnitrosamine-induced HCC. Intraperitoneal administration of diethylnitrosamine (DEN) was used to induce primary HCCs in male Sprague-Dawley rats. Magnetic resonance imaging (MRI) examinations were performed to follow the tumor formation and growth in the liver and H&E staining was used to confirm MR imaging findings. The rats with DEN treatment and control rats without DEN were euthanized at the time points of 3, 8, and 15 weeks after the start of modeling. 1 H NMR-based metabolomic analysis was used to explore hepatic metabolite changes and certify key metabolic pathways in the process of tumor tumorigenesis. Our MRI results depicted the formation of HCC nodules in ten rats 14 weeks after DEN injection which were confirmed by histology. Twenty-four different metabolites were identified and quantified by 1 H NMR spectroscopy; OPLS-DA models and corresponding VIP plots analysis further identified ten metabolites associated with the abnormal metabolism. The aberrant glucose, lipid, and glutathione-glutamine-glutamate metabolism could be detected involving in the process of hepatic tumorigenesis, which provides an important evidence for the in-depth study of subsequent molecular mechanisms, especially the glutathione-glutamine-glutamate metabolism.